Avoiding trouble ahead: Lessons learned and suggestions for economic evaluations of COVID-19 vaccines - Painter, C; Isaranuwatchai, W; Prawjaeng, J; Wee, HL; Chua, BWB; Huynh, VA; Lou, J; Goh, FT; Luangasanatip, N; Pan-Ngum, W; Yi, W; Clapham, H; et al. (Springer, 2021)
With vaccines for coronavirus disease 2019 (COVID-19) being introduced in countries across the world, policy makers are facing many practical considerations about how best to implement a vaccination programme. The supply of vaccines is insufficient for the global population, so decisions must be made as to which groups are prioritised for any vaccination and when. Furthermore, the aims of vaccination programmes will differ between countries, with some prioritising economic benefits that could stem from the relaxation of non-pharmaceutical interventions and others seeking simply to reduce the number of COVID-19 cases or deaths. This paper aims to share the experiences and lessons learned from conducting economic evaluations in Singapore and Thailand on hypothetical COVID-19 vaccines to provide a basis for other countries to develop their own contextualised economic evaluations, with particular focus on the key uncertainties, technical challenges, and characteristics that modellers should consider in partnership with key stakeholders. Which vaccines, vaccination strategies, and policy responses are most economically beneficial remains uncertain. It is therefore important for all governments to conduct their own analyses to inform local policy responses to COVID-19, including the implementation of COVID-19 vaccines in both the short and the long run. It is essential that such studies are designed, and ideally conducted, before vaccines are introduced so that policy decisions and implementation procedures are not delayed.